2018
DOI: 10.17576/ajag-2018-09-06
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Activity-based Costing in the Accountant General’s Department of Malaysia

Abstract: This research aims to provide insights into the process of implementing an Activity-Based Costing (ABC) system in the Accountant General's Department of Malaysia (AGD). Additionally, this paper examines the critical factors that influence the success of the ABC implementation process, the usefulness of the ABC system and the challenges faced during the process of implementation. Using a single case study approach, this research uses semi-structured interviews, a selfdeveloped questionnaire survey and a documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
2
0
8
Order By: Relevance
“…Nair and Tan (2018) agreed that whether the ABC system is integrated with other accounting systems or stands alone, compatibility with an existing IT system is an essential factor in the successful implementation of ABC. Wahab, Mohamad and Said (2018) suggested that the process of implementing an initiative may not be successful as a result of the barriers created by organisational defensive routines, which are threats to the acceptance of new ideas. The implications of organisational change, such as introducing ABC, should be considered within organisational and cultural contexts in which the change takes place because the human factor is important in any change of conditions (Kitsantas et al 2022).…”
Section: Information Technologymentioning
confidence: 99%
“…Nair and Tan (2018) agreed that whether the ABC system is integrated with other accounting systems or stands alone, compatibility with an existing IT system is an essential factor in the successful implementation of ABC. Wahab, Mohamad and Said (2018) suggested that the process of implementing an initiative may not be successful as a result of the barriers created by organisational defensive routines, which are threats to the acceptance of new ideas. The implications of organisational change, such as introducing ABC, should be considered within organisational and cultural contexts in which the change takes place because the human factor is important in any change of conditions (Kitsantas et al 2022).…”
Section: Information Technologymentioning
confidence: 99%
“…Sorros et al (2017) menemukan permasalahan utama rendahnya praktik adopsi akuntansi manajemen di organisasi sektor publik yaitu kurangnya sumber daya manusia terlatih serta biaya yang mahal. Sedangkan Abdul Wahab et al (2018) mengemukan dua alasan penyebabnya yaitu pertama proses dari teknik ABC itu sendiri sangat kompleks dan kedua kompleksitas organisasi sektor publik. Oleh karena itu, penelitian ini bertujuan untuk menyajikan gagasan kemungkinan implementasi ABC/M pada organisasi sektor publik khususnya organisasi pemerintah.…”
Section: Pendahuluanunclassified
“…Hasil temuan menunjukkan bahwa sebagian besar lembaga pendidikan di Yunani kesulitan mengalokasikan biaya secara akurat dan tidak mampu menerapkan metode ABC. Abdul Wahab et al (2018) menemukan bahwa proses pengembangan sistem ABC di Departemen Umum Akuntan Malaysia membutuhkan waktu yang cukup lama. Priyatmo & Akbar (2019) menganalisis penerapan metode ABC di salah satu Kantor Pelayanan Perbendaharaan Negara (KPPN) Jakarta menunjukkan bahwa metode ABC dapat digunakan untuk menghitung biaya produk per unit di KPPN Jakarta.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Most studies have shown that companies considering ABC implementation were concerned about the expenses required to implement and maintain the system (its implementation is time-consuming, and involves the entire organization, staff training, and setting up a project team). The aspects related to the system design, e.g., the identification of activities, or the determination of cost drivers, especially in small firms, seemed problematic (Cohen et al, 2005;Sartorius et al, 2007;Allain, & Laurin, 2018;Wahab et al, 2018). Akyol et al (2005) claimed that appropriate IT resources constituted an important factor that influenced the success of ABC implementation.…”
Section: Literature Reviewmentioning
confidence: 99%